DIRECTIVE UTTERANCES IN CINDERELLA MOVIE 2015 - Yehezkhiel Andi Pranata; Rr. Arielia Yustisiana (Humaniora Scientia, 2022)
The aim of the research is to know the types of directive utterances of Cinderella Movie 2015. Besides, the researcher wanted to know the functions of directive utterances in the Cinderella Movie 2015. This research used Kreidler’s theory to analyze those utterances in the Cinderella Movie 2015. The researcher used a qualitative approach as a research design. The data of this research were utterances which were taken from the Cinderella movie 2015 released on March 13, 2015. Then, the researcher classified the collected data based on the types of directives. After that, the researcher analyzed based on the function of directive utterances. The researcher analyzed the utterances in the movie which focused on the types of directive utterances. The research result was found about 35 directive utterances in Cinderella Movie 2015. The directive utterances in the movie were divided into three types: command, request, and suggestion. The command consisted of demand, direct, order and forbid. The request consisted of direct, order and forbid. Besides, the suggestion consists of advice and recommend. Based on the research, it was found seventeen (48,5%) while the request was found nine utterances (25,7%). There were nine utterances in suggestion (25,7%)Keywords: Directive Utterances, Types of Directive Speech Act, Cinderella Movie